PCDD and PCDF exposures among fishing community through intake of fish and shellfish from the Straits of Malacca - Azlan, Azrina; Mohamad Nasir, Nurul Nadiah; Shamsudin, Norashikin; Abdul Rahman, Hejar; Khoo, Hock Eng; Razman, Muhammad Rizal (BioMed Central, 2015)
Background: Exposure to PCDD/PCDF (dioxin and furan) through consumption of fish and shellfish is closely related to the occurrence of skin diseases, such as chloracne and hyperpigmentation. This study aimed to determine the exposure of PCDD/PCDF and its congeners in fish and shellfish obtained from different regions of the Straits of Malacca among the fishing community. Methods: The risk of fish and shellfish consumption and exposure to PCDD/PCDF among fishermen living in coastal areas of the Straits were evaluated based on a cross-sectional study involving face to face interviews, blood pressure and anthropometric measurements, and administration of food frequency questionnaires (FFQ). Skin examination was done by a dermatologist after the interview session. Determination of 17 congeners of PCDD/PCDF in 48 composite samples of fish and shellfish was performed based on HRGC/HRMS analysis. Results: The total PCDD/PCDF in the seafood samples ranged from 0.12 to 1.24 pg WHO-TEQ/g fresh weight (4.6-21.8 pg WHO-TEQ/g fat). No significant difference found for the concentrations of PCDD/PCDF between the same types of seafood samples obtained from the three different regions. The concentrations of the most potent congener, 2,3,7,8-TCDD in the seafood samples ranged from 0.01 to 0.11 pg WHO-TEQ/g FW (1.9 pg WHO-TEQ/g fat). A positive moderate correlation was found between the fat contents and concentrations of PCDD/PCDF determined in the seafood samples. The total PCDD/PCDF in all seafood samples were below the 1 pg WHO-TEQ/g fresh weight, with the exception of grey eel-catfish. The respondents had consumed fish and shellfish with the amounts ranging between 2.02 g and 44.06 g per person per day. The total PCDD/PCDF exposures through consumption of fish and shellfish among the respondents were between 0.01 and 0.16 pg WHO-TEQ/kg BW/day. With regard to the two PCDD/PCDF-related skin diseases, no chloracne case was found among the respondents, but 2.2 % of the respondents were diagnosed to have hyperpigmentation. Conclusion: Intake of a moderate amount of fish and shellfish from the area is safe and does not pose a risk for skin diseases. An over-consumption of seafood from the potentially polluted area of the Straits should be monitored in future.